Nanomaterials for electrochemical detection of pollutants in water: A review - Potes‐Lesoinne, Humberto Andre; Ramirez‐Alvarez, Fernando; Perez‐Gonzalez, Victor H.; Martinez‐Chapa, Sergio O.; Gallo‐Villanueva, Roberto Carlos (Electrophoresis, 2022)
The survival of living beings, including humanity, depends on a continuous supply of clean water. However, due to the development of industry, agriculture, and population growth, an increasing number of wastewaters is discarded, and the negative effects of such actions are clear. The first step in solving this situation is the collection and monitoring of pollutants in water bodies to subsequently facilitate their treatment. Nonetheless, traditional sensing techniques are typically laboratory‐based, leading to potential diminishment in analysis quality. In this paper, the most recent developments in micro‐ and nano‐electrochemical devices for pollutant detection in wastewater are reviewed. The devices reviewed are based on a variety of electrodes and the sensing of three different categories of pollutants: nutrients and phenolic compounds, heavy metals, and organic matter. From these electrodes, Cu, Co, and Bi showed promise as versatile materials to detect a grand variety of contaminants. Also, the most commonly used material is glassy carbon, present in the detection of all reviewed analytes.